A hypermobile prophage in the genome of a key human gut bacterium. - Andrey N Shkoporov; Colin Hill (PLoS Biology)
Phages infecting anaerobic bacteria are highly abundant in the mammalian gut, but their biology and ecological impact are poorly understood. A new PLOS Biology study provides a glimpse into the disruptive biology of the Hankyphages, parasites of the ubiquitous Bacteroidaceae.